New directions and perspectives in elastic instability and turbulence in various viscoelastic flow geometries without inertia - Steinberg, V (arXiv.org, 2022)
I shortly describe the main results on elastically driven instabilities and elastic turbulence in viscoelastic inertia-less flows with curved streamlines. Then I describe a theory of elastic turbulence and prediction of elastic waves at Re<<1 and Wi>>1, which speed depends on the elastic stress similarly to the Alfven waves in magneto-hydrodynamics and in in a contrast to all other fluid flows with wave speed depending on medium elasticity. Since the established and testified mechanism of elastic instability of viscoelastic flows with curvilinear streamlines becomes ineffective at zero curvature, so parallel shear flows are proved linearly stable, similar to Newtonian parallel shear flows. However, the linear stability of parallel shear flows does not imply their global stability. Here I switch to the main subject, namely a recent development in inertia-less parallel shear channel flow of polymer solutions. In such flow, we discover an elastically driven instability, elastic turbulence, elastic waves, and drag reduction down to relaminarization that contradicts the linear stability prediction. In this regard, I discuss shortly normal versus non-normal bifurcations in such flows, flow resistance, velocity and pressure fluctuations, and spatial and spectral velocity as a function of Wi at a high elasticity number.